EFFECTIVENESS OF ORIENTEERRING GAME BASED ON GOOGLE MAPS IN SCOUTING ACTIVITIES, TO GROW THE SOCIAL CHARACTER OF STUDENTS - Muhammad Luthfi; Rasimin Rasimin (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This study aims to determine the implementation of google maps-based orienteering games through scout activities and to determine the effectiveness of orienteering games on the social character of students at MI NU Hidayatul Mubtadiin Undaan Kudus. The method used in this study combines qualitative and quantitative methods or commonly called the mix method. By using descriptive qualitative and quantitative pre-experimental types. The results of this study are that the implementation of google maps-based oerinteering games in scout activities can be carried out using the concept of activity management which consists of pre-implementation which contains permits with the madrasah and the surrounding environment, preparation of the concept of step-by-step implementation, setting orienteering game routes, and determining mission completion targets. And the implementation concept consisting of the opening ceremony, departure ceremony, share the orienteering game route links to the participants, work out missions between posts, and closing. Orienteering games based on google maps in scout activities are quite effective in fostering the social character of MI NU Hidayatul Mubtadiin Undaan Kudus students. Based on the data testing the hypothesis using the t test with the acquisition of sig = 0.000, which means less than 0.05. thus, Ho is rejected and Ha is accepted. And the N-Gain test with a score of 0.574 which is classified as moderate effectiveness.